The Effectiveness of Progressive Muscle Relaxation and Mozart Music Therapy on Premenstrual Syndrome Stress Scores - Fina Nurul Azizah; Sri Sumarni; Farida Sukowati; Suryati Kumorowulan (JURNAL KEBIDANAN, 2021)
The incidence of premenstrual syndrome is high. Premenstrual syndrome sufferers feel disturbed with the symptoms. One of these symptoms is stress. Stress can reduced by progressive muscle relaxation and Mozart's music therapy. The purpose of study was to determine the effectiveness of progressive muscle relaxation and Mozart's Music therapy on the stress of premenstrual syndrome.This study used quasy experiment with nonquivalent control group design. The population was 89 midwifery students Health Polytechnic Semarang. The sample was 50 people divided into two groups with purposive sampling technique. The results showed there was an effect of progressive muscle relaxation on  premenstrual syndrome stress score (p-value : 0.001 ) with the average score decrease 5.32. It also showed that there was an effect of Mozart's Music therapy on premenstrual syndrome stress scores (p-value : 0.001 ) with the average score decrease 2.8. Different test between two groups was found that there were differences in effectiveness of progressive muscle relaxation and Mozart's music therapy on premenstrual syndrome stress scores (p-value : 0.008). Progressive muscle relaxation is more significant reducing premenstrual syndrome stress score.The research place suggested to apply progressive muscle relaxation and Mozart music therapy to students who experience stress in premenstrual syndrome